Aktivitas antioksidan dan hedonik teh hijau berbahan baku daun mangrove Avicennia sp. dan Sonneratia sp.: Antioxidant activity and hedonic of green tea made from mangrove leaves Avicennia sp. and Sonneratia sp. - Hasibuan, Nirmala Efri; Azka, Aulia; Ratrinia, Putri Wening; Sumartini, Sumartini; Pamaharyani, Luchiandini Ika; Suryono, Muh; Basri, Basri (Jurnal Pengolahan Hasil Perikanan Indonesia, 2025)
Green tea has long been known as a beverage with various health benefits, especially because of its high antioxidant content. Mangrove leaves are potential raw materials for green tea because they contain secondary metabolite compounds that act as antioxidants. This study aims to determine the best mangrove species that have the potential to be green tea through chemical parameters, antioxidants, and hedonic assessments. Green tea was produced from young leaves at the top of the mangrove Avicennia sp. and Sonneratia sp. obtained from the Bandar Bakau ecosystem area, Dumai City, and commercial tea (Camellia sinensis) for comparison. The analyzed parameters included chemical characteristics (moisture content, ash, acid-insoluble ash, water-soluble extract, and fiber), phytochemicals, percentage of antioxidant inhibition by the DPPH method, and hedonic assessments (taste, aroma, color, and overall). The results showed that the three types of tea had a moisture content of 7.84-25.45%, ash 6.69-16.12%, acid-insoluble ash 0.65-1.23%, water-soluble essence 2.82-4.27%, and fiber 5.80-7.11%. Phytochemical compounds were more frequently detected in commercial tea than in mangrove leaf tea. Differences in the types of green tea raw materials significantly affected the percentage of antioxidant inhibition and the hedonic assessment of the panelists. The best treatment of green tea with Sonneratia sp. mangrove leaves had the highest percentage of antioxidant inhibition (87.59%), and the overall hedonic assessment was highly favored by panelists. This tea meets the green tea standards according to SNI 3945:2016 in ash content, acid-soluble ash, and crude fiber, but not in moisture content or water-soluble essence. The results of this study indicate that mangrove leaves have potential as a raw material for green tea production.